The impact of electrical injuries on long-term outcomes: A Burn Model System National Database study. Issue 2 (March 2020) - Stockly, O.R.; Wolfe, A.E.; Espinoza, L.F.; Simko, L.C.; Kowalske, K.; Carrougher, G.J.; Gibran, N.; Bamer, A.M.; Meyer, W.; Rosenberg, M.; Rosenberg, L.; Kazis, L.E.; et al.
Highlights: Adults with electrical injuries demonstrated worse physical functioning at 24 months post-injury than those with fire/flame injuries. Adults with electrical injuries were nearly half as likely to be employed at 24 months post-injury than those with fire/flame injuries. Results suggest a need for examination of return to work, work accommodations and performance at work following electrical injuries. Abstract: Introduction: Electrical injuries exhibit significant acute and long-term sequelae. Amputation and neurological deficits are common in electrical injury survivors. There is a paucity of information on the long-term outcomes of this population. Therefore, this study examines the long-term outcomes of electrical injuries by comparing them to fire/flame injuries. Methods: Data from the Burn Model System National Database collected between 1996 and 2015 was examined. Demographic and clinical characteristics for adult burn survivors with electrical and fire/flame injuries were compared. Satisfaction With Life Scale (SWLS), Short Form-12 Physical Composite Score (SF-12 PCS), Short Form-12 Mental Composite Score (SF-12 MCS), and employment status were examined at 24 months post-injury. Linear and logistic regression models were used to assess differences in outcome measures between groups, controlling for demographic and clinical variables. Results: A total of 1147 adult burn survivors (111 with electrical injuries; 1036 with fire/flame injuries) were included in this study. Persons with electrical injuries were more likely to be male and injured at work (p < 0.001). SF-12 PCS scores were significantly worse for survivors with electrical injuries at 24 months post-injury than survivors with fire/flame injuries (p < 0.01). Those with electrical injuries were nearly half as likely to be employed at 24 months post-injury than those with fire/flame injuries (p = 0.002). There were no significant differences in SWLS and SF-12 MCS between groups. Conclusions: Adult survivors with electrical injuries reported worse physical health and were less likely to be employed at 24 months post-injury compared to survivors with fire/flame injuries. A more detailed understanding of return to work barriers and work accommodations is merited for the electrical injury population. Furthermore, the results of this study should inform future resource allocation for the physical health and employment needs of this population.